Her time, his time, or the maid's time: An analysis of the demand for domestic work - Elena G. F. Stancanelli; Leslie Sundt Stratton (Institute for the Study of Labor (IZA), 2010)
This paper analyzes households' demand for time inputs to domestic services, modeling simultaneously the decision to purchase services in the market and the time spent on weekend and weekday days by each partner on routine household chores. By focusing on cleaning, laundry, and ironing, we reduce the likelihood that preferences matter and increase the overlap with market services. Particular emphasis is placed on estimating the effects of prices, as captured by own and partner wages and the market price for domestic services. We exploit time-diary data for Great Britain and France, relying on cross-country comparisons to generalize our findings. The results indicate that prices strongly influence market purchases, and that maid service is a closer substitute for household time on weekends than weekdays, but is also correlated with 'her' weekday time. More generally, we find that women's wages have a stronger association with the inputs to domestic work than any other price measure.
Keywords: J22; J16; 330; time use; domestic work; gender